2017
DOI: 10.1002/cncr.31126
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia: Are we ready to take a step forward?

Abstract: The field of cancer cachexia at both the preclinical and clinical levels will benefit from the further investigation and refinement of its mechanisms and further study of potential agents to define the best treatment outcomes for patients. In the meantime, the availability of anamorelin, a promising agent in the clinic, would be extremely valuable to move that research forward. See also pages 606‐16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…One of the classifications for cachexia is a BMI < 20kg/m² 48 . This syndrome is associated with deterioration of patient's quality of life 49,50 , confirming the findings of this study, in which underweight patients reported poorer global health status/quality of life after the onset of treatment, when compared to those in their normal weight range. One explanation for this deteriorated quality of life is the increased toxicity inherent to the treatment, due to loss of muscle 47 .…”
Section: Discussionsupporting
confidence: 87%
“…One of the classifications for cachexia is a BMI < 20kg/m² 48 . This syndrome is associated with deterioration of patient's quality of life 49,50 , confirming the findings of this study, in which underweight patients reported poorer global health status/quality of life after the onset of treatment, when compared to those in their normal weight range. One explanation for this deteriorated quality of life is the increased toxicity inherent to the treatment, due to loss of muscle 47 .…”
Section: Discussionsupporting
confidence: 87%
“…The secondary types of toxic side effects of cisplatin are gastrointestinal toxicity and hematological toxicity. The former includes nausea and vomiting (CINV), anorexia, weight loss, and diarrhea. Among them, CINV is the most common side effect of cisplatin. More than 90% of patients develop it in the clinic.…”
Section: Clinical Toxic Side Effects Of Cisplatinmentioning
confidence: 99%
“…Multiple aetiologies, including chemotherapy for cancer (Murtaza et al ., ; Jeter et al ., ), Alzheimer's disease (Sergi et al ., ; Boesveldt et al ., ), sinonasal disease and anosmia (Whitcroft et al ., ), can lead to poor appetite and potential malnutrition. Furthermore, cancer associated cachexia patients (Werner et al ., ; Baracos et al ., ; Crawford, ), could significantly benefit from development of high‐nutrient functional food products with soft texture characteristics as an aid to ease swallowing.…”
Section: Discussionmentioning
confidence: 99%